Beban Kerja Petugas Administrasi Klaim BPJS Kesehatan Di Puskesmas Mamajang - Aripa, Lusyana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The large number of activities carried out and the responsibility for the work carried out, means that administrative staff experience a high workload so that it must be a concern for the Mamajang Makassar Community Health Center to take important steps, namely by adding administrative staff, or by adding facilities and infrastructure such as: computers, printers and Wifi as well as transportation accommodation so that work can be facilitated at the Mamajang Community Health Center. Research Objective To find out in depth the workload of BPJS Health claims administration officers at the Mamajang Community Health Center. This type of research is qualitative descriptive research. The data collection methods used were observation, interviews, and document review. And the data analysis used in this research uses a qualitative descriptive data analysis method, with steps for data reduction, data presentation, and drawing conclusions. Workload analysis shows a mismatch between time pressure and workload, caused by factors such as working hours, limited facilities, additional tasks, and problems managing patient information. Analysis of the workload of BPJS Health claims administration officers at the Mamajang Community Health Center highlights information overload, including limited facilities, work outside working hours, lack of data analysis, and stress from interactions with patients. Analysis based on responsibilities shows the complexity of the responsibilities of BPJS Health Mamajang administrative officers, from claims to interactions with patients. Environmental constraints, limited facilities, and difficulties in communicating with patients are the main obstacles.